Fundamentals of embedded software:where C and assembly meet - Lewis, Daniel W. (New Delhi : Prentice Hall of India, 2005)
Computer science
Keywords: Embedded software; Embedded system; Assembly meet; Data representation; Computer organization; Input programming; Output Programming; Concurrent software; Scheduling; Memory Management; Shared Memory; Programming project